Chitosan Matrix Encapsulation of α‐Lipoic Acid (LA) Anchored Gold Nanoparticles: A Combined Experimental and Theoretical Study. Issue 38 (11th October 2021) - Gunupuru, Ravi; Mehrotra, Amritansh; Sairam, Pinisetti Swami; Vyas, Gaurav; Pandey, Jitendra K; Sen, Anik
Abstract: In this article the competitive binding of citrate (2‐hydroxypropane‐1, 2, 3‐tricarboxylate), chitosan and α‐lipoic acid ((R)‐5‐(1, 2‐dithiolan‐3‐yl) pentanoic acid, (LA) are tested on the surface of Gold Nanoparticle (AuNP). The chitosan matrix encapsulated gold nanoparticle resulted in colour reversibility in presence of α‐lipoic acid through partial ligand exchange mechanism. Different experimental analysis including TEM, EDX, spectrophotometry and FTIR were spectrometry performed to check the interaction mechanism and explain the colour reversibility. Binding and colour reversibility mechanism was also supported through the Density functional Theory calculations. Abstract : Competitive binding of citrate (2‐hydroxypropane‐1, 2, 3‐tricarboxylate), chitosan and α‐lipoic acid ((R)‐5‐(1, 2‐dithiolan‐3‐yl) pentanoic acid were performed which showed a colour change from red to purple violet on addition of chitosan on the citrate interacted AuNP, which reverted back to the pink‐red colour on addition of α‐lipoic acid. TEM, EDX, FTIR and Density Functional theory calculations explained the reason behind the binding interactions of the various ligands and the colour reversibility pattern of the AuNPs.